Lipoma Arborescens in Childhood: A Report of Two Sisters - Gülümser AYDIN; Işık KELEŞ; Özgür TOSUN; Aliye TOSUN; Latife Özlem YILMAZ; Tuba Kendi KARAGÜLLE; Sevim ORKUN1 (Archives of Rheumatology, 2012)
Lipoma arborescens (LA) is a rare benign lesion of synovial joints and bursae. The knee is the most common site of the involvement. Magnetic resonance imaging findings are typical in the diagnosis. The number of case reports of LA in children is significantly lower compared to the adults. In this article, two nine-year-old and 15-year-old sisters who were examined for the complaints of bilateral pain and swelling in knees were presented. Magnetic resonance imaging demonstrated typical features of LA in the right knees of both children. Pediatric patients with mono/oligoarticular effusion and synovial hypertrophy without systemic involvement, LA should be considered in differential diagnosis. Magnetic resonance imaging is a sensitive modality in the diagnosis of LA.